Planning Evaluasi Pembelajaran Menggunakan Aplikasi Al-Qur’an Kemenag - Kusumawati; Idris Tumnenggung, Ham (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The research method uses analytical descriptive with triangulation actions carried out so as to determine the final results of the analysis as follows; 1) Preparation and Observation, attendance, RPS, theoretical basis, student ability data and explaining the Qur'an as a source of Islamic law. 2) Taking data from the mid-term exam summative test. 3) giving the name of the surah and verses to the specified surah number. 4) looking for the mention of the word al-Qur'an in juz 1-5. 5) looking for the mention of the word al-Qur'an in the specified QS. 6) giving a questionnaire for Learning Evaluation Planning Using the Ministry of Religion's Al-Qur'an Application. With the results of the study, as many as 4 (2.6%) respondents always read the Qur'an on mobile applications with various branch markets, 9 (13.8%) often, 21 (32.3%) sometimes, 7 (10.7%) never read the Qur'an using the application. A total of 12 (18.5%) respondents always chose to use applications other than the Ministry of Religious Affairs' Al-Qur'an as learning media, 14 (21.5%) often, 31 (47.6%) sometimes, 5 (7.6%) respondents never chose to use applications other than the Ministry of Religious Affairs' Al-Qur'an as learning media. The obstacles in using the Al-Qur'an application were not too difficult due to the respondents' basic study of informatics engineering, the use of applications other than the Ministry of Religious Affairs' Al-Qur'an application in Islamic religious education learning, respondents used Pro Muslim, Al-Qur'an Indonesia, NU online, and Google Browser.